“She Can Bother Me, and That’s Because She Cares”: What Inuit Students Say About Teaching and Their Learning - Lewthwaite, Brian; McMillan, Barbara (Canadian Journal of Education/Revue canadienne de l'éducation, 2010)
In this study, we have investigated, through interviews, conversations, question‐ naires, and observations, perceptions of learning success of northern Qikiqtani (Baffin Island) of Nunavut Inuit middle years (grades 5‐8) students and the classroom ped‐ agogy influencing their success, in particular their learning in science. Most of the processes identified as contributors to successful learning were culturally located. Students also placed importance on teachers who cared not only for them as people, but also for their performance as learners. Based upon students’ information, we have presented a profile of the characteristics of effective teachers in Inuit schools to pro‐ mote learning within a positive environment. Key words: Nunavut, culturally responsive teaching, social and interactive processes, Qikiqtani (Baffin Island) Les auteurs ont étudié, à l’aide d’entrevues, de conversations, de questionnaires et d’observations, les perceptions d’élèves de 5e à 8e année sur l’île de Baffin au Nunavut au sujet des facteurs entrant en jeu dans leur réussite scolaire, notamment en sciences. La plupart des facteurs identifiés étaient reliés à la culture locale. Les élèves accor‐ daient en outre de l’importance aux enseignants qui se souciaient d’eux non seule‐ ment comme personnes mais aussi comme apprenants. À la lumière des entrevues effectuées, les auteurs brossent un tableau des caractéristiques d’enseignants efficaces qui réussissent à promouvoir l’apprentissage dans des écoles inuites, dans un envir‐ onnement positif. Mots clés : Nunavut, enseignement adapté à la réalité culturelle, processus sociaux et interactifs, Qikiqtani (île de Baffin).